ANALISIS PERBEDAAN RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM SAAT PANDEMI DIBANDING SEBELUM PANDEMI COVID-19 DI INDONESIA - Nila Diansari; Muhammad Faisal Abdullah; Yunan Syaifullah (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to see and analyze the differences in stock returns and trading volume of shares of transportation companies on the Indonesia Stock Exchange during the pandemic compared to before the Covid-19 pandemic in Indonesia. This study uses stock prices and stock trading volume on the Indonesia Stock Exchange from November 2019 to July 2020. The data analysis method used was the Kolmogorof Smirnov normality test and the Wilcoxon Signed Rank Test. The research results there is a significant difference in the stock returns of transportation companies during the Covid-19 pandemic compared to before the Covid-19 pandemic in Indonesia and there is a significant difference in the trading volume of shares of transportation companies during the Covid-19 pandemic compared to before the Covid-19 pandemic in Indonesia